$$\\\frac{-2}{3}\div\frac{-6}{7}\\\\ =\frac{-2}{3}\times\frac{7}{-6}\\\\ =\frac{1}{3}\times\frac{7}{3} \qquad $I have divided top and bottom by $ -2\\\\ =\frac{7}{9}\\\\$$

negative times a negative will be positive, then just multiply the numerators across (2x6) 12 and then the denominators (3x7) 21. Reduce 12/21 by dividing both the numerator and denominator by 3 and the reduced or simplist form is +4/7.

$$\\\frac{-2}{3}\div\frac{-6}{7}\\\\ =\frac{-2}{3}\times\frac{7}{-6}\\\\ =\frac{1}{3}\times\frac{7}{3} \qquad $I have divided top and bottom by $ -2\\\\ =\frac{7}{9}\\\\$$